Variability of Dissolved Oxygen in the Bottom Layer of the Southern Senegalese Shelf. Issue 5 (19th May 2021) - Tall, A. W.; Machu, E.; Echevin, V.; Capet, X.; Pietri, A.; Corréa, K.; Sall, S. M.; Lazar, A.
Abstract: The observation station "Melax" was deployed in 2015 on the wide and shallow south Senegalese shelf to study the ocean dynamics, air‐sea interactions, and dissolved oxygen (DO) cycle. Data from February 2015 to August 2016 were used to study the main physical processes affecting the variability of DO in the bottom layer (∼30 m depth) on time scales ranging from tidal to seasonal. Between November and May, wind‐driven upwelling provides phytoplankton enrichment of the surface layers and brings cold, salty, and depleted DO on the shelf. Water properties at Melax vary depending on the source waters located at the shelf edge. The DO concentration changes between the shelf edge and Melax are broadly consistent with the inferred respiration rates estimated in previous studies. In contrast, the monsoon season (July–October) is characterized by weak westerly winds and northward currents. Bottom waters are warmer, fresher, and more oxygenated. The slower circulation in this period allows a stronger decoupling between the water properties of the waters observed at Melax and those of the source waters. Stratification strengthening near the bottom layer inhibits vertical mixing and induces strong high‐frequency variability in properties caused by internal tide‐generated waves. Intense upwelling events can deepen the mixed layer and intermittently transform the bottom layer waters (locally or remotely). Relaxation events associated with current reversals significantly modify their properties. Coastal trapped waves constitute a distant forcing that can act year‐round, impacting both shelf waters and source regions. Plain Language Summary: Global warming and extra nutrient loads from agriculture and waste‐waters reduce the oxygen content in the ocean. Incidentally, oxygen‐depleted waters are encountered with increased frequency oceanwide and this trend is more pronounced in coastal environments. Temperature and oxygen impact the metabolism of marine organisms and their variations can be major sources of (natural or anthropogenic) stresses. We used here measurements made at a fixed monitoring buoy (Melax) located over the southern Senegalese mid‐shelf (35 m depth) to study the variability of bottom oxygen (the surface being well oxygenated). Its seasonality is constrained by the circulation and the wind regime. They induce the transport of deep, colder, saltier, and less oxygenated waters from the shelf break onto the shelf during the upwelling season compared to the monsoon season. The properties of water masses on the shelf thus depend on those of the water masses drawn from the open ocean through the shelf break which can be modified by many processes acting over a wide range of scales from days to seasons and longer. On the shelf, respiration of organic matter reduces oxygen whereas diurnal wind variability and internal tides oxygenate bottom layers when the water column is stratified. Key Points: Relaxation periods between upwelling events generate poleward transport of warm and oxygen‐rich shelf waters Internal waves generate daily to infra‐daily oscillations of oxygen over a density‐stratified shelf during the warm season Mid‐shelf dissolved oxygen reflects open ocean properties with changes consistent with estimated respiration rates during upwelling season